2006
DOI: 10.1007/s00441-006-0306-1
|View full text |Cite
|
Sign up to set email alerts
|

Enameloid/enamel transition through successive tooth replacements in Pleurodeles waltl (Lissamphibia, Caudata)

Abstract: Study of the evolutionary enameloid/enamel transition suffers from discontinuous data in the fossil record, although a developmental enameloid/enamel transition exists in living caudates, salamanders and newts. The timing and manner in which the enameloid/enamel transition is achieved during caudate ontogeny is of great interest, because the caudate situation could reflect events that have occurred during evolution. Using light and transmission electron microscopy, we have monitored the formation of the upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…Odontoblasts progressively reduced their production of loose collagenous matrix, which characterizes forming enameloid, while ameloblast activity increased with the secretion of large amounts of enamel-specific products at the dentin surface. This evolutionary 'tran sition' between enameloid and enamel was, in fact, probably an enameloid-dentin transition, as recently demo nstrated in the ontogeny of caudate amphibians [Davit-Béal et al, 2007]. However, enamel did not replace enameloid in all vertebrate lineages.…”
Section: Enamel/enameloid and The Origin Of Empsmentioning
confidence: 99%
“…Odontoblasts progressively reduced their production of loose collagenous matrix, which characterizes forming enameloid, while ameloblast activity increased with the secretion of large amounts of enamel-specific products at the dentin surface. This evolutionary 'tran sition' between enameloid and enamel was, in fact, probably an enameloid-dentin transition, as recently demo nstrated in the ontogeny of caudate amphibians [Davit-Béal et al, 2007]. However, enamel did not replace enameloid in all vertebrate lineages.…”
Section: Enamel/enameloid and The Origin Of Empsmentioning
confidence: 99%
“…[13] Although these tissues are similar when mineralized, they differ in structure and organization of their organic matrix. [14] Dental tissues are complex hydrated biological composites consisting of inorganic material, organic components and water. The composition of these materials, and their interaction, will determine the mechanical properties of the individual dental tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Enameloid develops from dental epithelial and odontoblast activity, and it is composed, at least initially, of matrices containing predominantly collagen (Sasagawa et al 2009). This suggests that enameloid may be associated with dentin formation and is thus different from enamel (Davit-Beal et al 2007;Assaraf-Weill et al 2014). While it is not fully understood if enameloid and enamel are related evolutionarily, it has been shown that several species (newts, salamanders, some fish) that produce enameloid structures also have a mineral coating that appears to be enamel, since it is synthesized by ameloblasts Davit-Beal et al 2007;Diekwisch et al 2009).…”
Section: Introduction To the Evolution Of Enamel Structurementioning
confidence: 99%
“…This suggests that enameloid may be associated with dentin formation and is thus different from enamel (Davit-Beal et al 2007;Assaraf-Weill et al 2014). While it is not fully understood if enameloid and enamel are related evolutionarily, it has been shown that several species (newts, salamanders, some fish) that produce enameloid structures also have a mineral coating that appears to be enamel, since it is synthesized by ameloblasts Davit-Beal et al 2007;Diekwisch et al 2009). These layers reveal structural and compositional characteristics of enamel, since their matrices are composed of tuftelins, enamelins, amelogenins, and enamel-specific enzymes (Diekwisch et al 2002;Satchell et al 2002).…”
Section: Introduction To the Evolution Of Enamel Structurementioning
confidence: 99%
See 1 more Smart Citation